Diagnostic Accuracy of Multidetector Computed Tomography in Detecting Mesorectal Fascia Involvement in Colorectal Carcinoma - Panezai, Mahrukh; Anwar, Javed; Khattak, Abdul Latif; Amir, Omar; Tareen, Ayesha; Saleem, Humera (Pakistan Armed Forces Medical Journal, 2022)
Objectives: To determine the diagnostic accuracy of multi detector computed tomography (MDCT) in detecting mesorectal fascia involvement in colorectal carcinoma, taking histopathology as a gold standard. Study Design: Cross-sectional study. Place and Duration of Study: Department of Radiology, Combined Military Hospital Quetta from Jun to Dec 2019. Methodology: A total of 117 suspected patients of colorectal carcinoma, aged 40-80 years of either gender were included. All the patients underwent MDCT and then were looked for mesorectal fascia involvement. After surgical intervention, the his to pathological result of respected specimens was correlated with MDCT findings. Results: MDCT showed mesorectal fascia involvement in 66 (56.41%) patients. Histopathology confirmed mesorectal fascia involvement in 62 (52.99%) cases, whereas 55 (47.01%) patients revealed no mesorectal fascia involvement. In MDCT positive patients, 56 patients were true positive, while ten patients were false positive. Among 51 MDCT negative patients, 6 were false-negative while 45 were true negative. Overall results of sensitivity, specificity, positive predictive value, negative predictive value, and diagnostic accuracy of MDCT in detecting mesorectal fascia involvement, taking histopathology as the gold standard was, 90.32%, 81.82%, 84.85%, 88.24% and 86.32% respectively. Conclusion: This study concluded that MDCT is a recommended modality due to its high sensitivity. It is an accurate modality for pre-operative detecting mesorectal fascia involvement in colorectal carcinoma patients.